Relasi Antara Penggunaan Android dan Perubahan Sosial Perdesaan: Studi Perubahan Sosial di Kabupaten Bogor Jawa Barat - Iskandar Zulkarnain; Husaini Husaini; Khamid Baekhaki; F. Yoppie Christian (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2016)
Social changes is all changes on social institutions within community which impacting on its system including values, norms and patern of behaviour between groups in community, technology is one of the cause. Technology of media cq Android pressumed will give impact on traditional rural so-cial system, thus these mixed-method research intended to study how far the impact of the usage of Android on rural social changes. The present of internet followed by the more personalized Android in the rural community has made a transformation on interaction dimension between member of community both in Babakan village as urban-rural, and Petir as rural-village. The ownership and usage of Android between member of community today has various of meanings, whether to build peer-relation, tighten the family cohesion or to support the economic activities. The social change as impact of the usage of Android apparrently only occurs on interaction dimension without changing the structural or the cultural dimension. Research found, the prolonged social norms which has been rooted and maintaned by the community still able to work as social control mechanism, however the research shows the indication that the rationlisation on individual is ongoing, this may more or less loosen the social cohesion of rural community.